Answer:
Second option: (-2,-3) and (1,0)
Explanation:
Given the system of equations
, you can rewrite them in this form:
![x^2 + 2x-3= x - 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ebcue211e764tmnsqkqzphdzjwqn670ga7.png)
Simplify:
Factor the quadratic equation. Choose two number whose sum be 1 and whose product be -2. These are: 2 and -1, then:
![(x+2)(x-1)=0\\\\x_1=-2\\\\x_2=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j5hsjszn3z268m3bxt2xxh43jvg55wabtt.png)
Substitute each value of "x" into any of the original equation to find the values of "y":
![y_1= (-2) - 1=-3\\\\y_2=(1)-1=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kenw3860qsfxjh4p6l0f4lx1hz6reu3g97.png)
Then, the solutions are:
(-2,-3) and (1,0)